2022
DOI: 10.1136/bmjopen-2021-053242
|View full text |Cite
|
Sign up to set email alerts
|

Comparing effects of obesity treatment with very low energy diet and bariatric surgery after 2 years: a prospective cohort study

Abstract: ObjectivesTo compare long-term effects and complications of medical treatment (MT) of obesity including very low energy diet with bariatric surgery.Design and settingThis prospective study conducted in a clinical setting recruited individuals with body mass index (BMI) ≥35 kg/m2 referred for obesity treatment. Demographic and anthropometric data, laboratory samples, and questionnaire replies were collected at baseline and 2 years.Participants and interventions971 individuals were recruited 2015–2017. 382 recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…The BMI of the participants in the current study was reduced after 2 years only in the surgically treated group. In the main study BASUN, a decrease in BMI was seen both in the medically and the surgically treated patients, even if the weight reduction was greater in the surgically treated group [Höskuldsdottir et al, 2022]. Both medical and surgical obesity treatment have been shown to be effective regarding weight loss [Ma et al, 2017;Lean et al, 2018], although most studies do not compare those treatments but have "care as usual" as a control group.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…The BMI of the participants in the current study was reduced after 2 years only in the surgically treated group. In the main study BASUN, a decrease in BMI was seen both in the medically and the surgically treated patients, even if the weight reduction was greater in the surgically treated group [Höskuldsdottir et al, 2022]. Both medical and surgical obesity treatment have been shown to be effective regarding weight loss [Ma et al, 2017;Lean et al, 2018], although most studies do not compare those treatments but have "care as usual" as a control group.…”
Section: Discussionmentioning
confidence: 94%
“…Both medical and surgical obesity treatment have been shown to be effective regarding weight loss [Ma et al, 2017;Lean et al, 2018], although most studies do not compare those treatments but have "care as usual" as a control group. It might be hypothesized that the intestinal differences in anatomy after RYGB and SG could have an impact, for example, on nutritional and hormonal status with subsequent consequences [Sumithran et al, 2011;Höskuldsdottir et al, 2022]. At the start of BASUN, RYGB was the predominant obesity surgery method in Sweden while SG surgeries increased during the inclusion period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is associated with an increased risk of type 2 diabetes, dyslipidemia, sleep apnea, coronary heart disease, deterioration in quality of life and increased mortality 1–3 . Bariatric surgery achieves rapid, significant, and sustained weight loss (WL) as well as remission of obesity‐related comorbidities and overall mortality 4–6 . Observational studies have reported that the greatest WL occurs in the first 2 years after bariatric surgery 7 .…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 , 3 Bariatric surgery achieves rapid, significant, and sustained weight loss (WL) as well as remission of obesity‐related comorbidities and overall mortality. 4 , 5 , 6 Observational studies have reported that the greatest WL occurs in the first 2 years after bariatric surgery. 7 However, 15%–35% of patients do not reach their WL goal in the first 2 years after the procedure.…”
Section: Introductionmentioning
confidence: 99%